2018
DOI: 10.1111/joic.12546
|View full text |Cite
|
Sign up to set email alerts
|

Permanent pacemaker implantation after transcatheter aortic valve replacement in bicuspid aortic valve patients

Abstract: Excessive perimeter oversizing in relation to aortic annulus and depth of implantation greater than 6 mm should be avoided to improve PPI post-TAVR for BAV patients receiving self-expanding devices, especially for type 1 BAV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…We observed that the rate of PPI was significantly lower in patients who were treated with J-Valve (4.3%) than in those who were re-ported with Edwards SAPIEN 22,23) or Medtronic Core-Valve 24) or other THVs. 11,25,26) We speculated the reasons for the lower rate of PPI in patients using J-Valve as follows: (1) The connecting sutures between valve body and positioning element 7) can prevent deep positioning of the prosthesis within left ventricular outflow tract during THV In TAVI procedure, this is an effective way to avoid the complete AV block that may directly result from the compression caused by THV devices, 27) leading to a lower incidence of third-degree AV block. (2) The lesser radial force of support frame could reduce excessive compression on calcified aortic valve/annular, which may be FRAME DESIGN OF PROSTHESIS AFFECT TAVI RESULTS another contributing factor to this advantage of J-Valve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that the rate of PPI was significantly lower in patients who were treated with J-Valve (4.3%) than in those who were re-ported with Edwards SAPIEN 22,23) or Medtronic Core-Valve 24) or other THVs. 11,25,26) We speculated the reasons for the lower rate of PPI in patients using J-Valve as follows: (1) The connecting sutures between valve body and positioning element 7) can prevent deep positioning of the prosthesis within left ventricular outflow tract during THV In TAVI procedure, this is an effective way to avoid the complete AV block that may directly result from the compression caused by THV devices, 27) leading to a lower incidence of third-degree AV block. (2) The lesser radial force of support frame could reduce excessive compression on calcified aortic valve/annular, which may be FRAME DESIGN OF PROSTHESIS AFFECT TAVI RESULTS another contributing factor to this advantage of J-Valve.…”
Section: Discussionmentioning
confidence: 99%
“…24) Moreover, THVs with a long self-expandable stent such as CoreValve prosthesis will be deployed in a deeper position in the left ventricular outlet flow than that with short cylinder stent (Edwards SAPIEN or J-Valve) during TAVI procedure, which may increase the probability to compress cardiac conduction system. 27) Bicuspid aortic valve is more frequently observed in patients who candidate for TAVI in China. The patients with bicuspid aortic valve had severer native aortic valve calcification than the individuals with tricuspid aortic valve.…”
Section: Discussionmentioning
confidence: 99%
“…After dedicated literature search and selection, 9 studies were included in the final pooled-analysis ( 9 , 10 , 16 22 ). Study quality was evaluated by Newcastle-Ottawa Scale ( Table 1 ) and there was generally a low risk of bias in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…No difference was found between type 1 and type 0 with regard to other procedural characteristics. In the 9 included studies, 4 were SEV-specific ( 9 , 10 , 16 , 22 ) and in the other 5 studies both SEV and BEV were used. In the study of Yoon et al, statistically lower proportion of type 1 received SEV compared to type 0 ( 20 ), but in the other studies there was no such difference.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation